(untitled) (Bangladesh Journal of Pharmacology, 2012)
New drugs for the inhibition of the enzyme aldose reductase are in development and they have to be screened before being considered for preclinical and clinical evaluation. The current study deals with the evaluation of the cyclooxygenase inhibitory activity of flavonoids using in silico docking studies. In this perspective, flavonoids like bergapten, buceracidin-B, dorsilurin-F, communin-A, and coumestrol were selected. Epalrestat, a known aldose reductase inhibitor was used as the standard. Docking results showed that all the selected flavonoids showed binding energy ranging between -7.91 kcal/mol to -5.08 kcal/mol when compared with that of the standard (-5.59 kcal/mol). Intermolecular energy (-9.11 kcal/mol to -8.66 kcal/mol) and inhibition constant (1.58 µM to 187.37 µM) of the ligands also coincide with the binding energy. Communin-A contributed better aldose reductase inhibitory activity because of its structural parameters.